2019
DOI: 10.3390/w11081599
|View full text |Cite
|
Sign up to set email alerts
|

Hydropower from the Alpine Cryosphere in the Era of Climate Change: The Case of the Sabbione Storage Plant in Italy

Abstract: Greenhouse gas reduction policies will have to rely as much as possible upon renewable, clean energy sources. Hydropower is a very good candidate, since it is the only renewable energy source whose production can be adapted to demand, and still has a large exploitation margin, especially in developing countries. However, in Europe the contribution of hydropower from the cold water in the mountain areas is at stake under rapid cryospheric down wasting under global warming. Italian Alps are no exception, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…It would be of interest to analyze changes in hydropower production when introducing an operation from a reservoir, and optimal management thereby. This would allow storage during the low demand period (winter), and production during summer, when hydropower demand will be the largest under climate change, possibly with increasing revenues [10,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be of interest to analyze changes in hydropower production when introducing an operation from a reservoir, and optimal management thereby. This would allow storage during the low demand period (winter), and production during summer, when hydropower demand will be the largest under climate change, possibly with increasing revenues [10,31].…”
Section: Discussionmentioning
confidence: 99%
“…Stucchi et al [31] analyzed the Sabbione glacier (ca. 100 km northeast of Chavonne), and from ICA = 2.9 km 2 , IWE = 53.7 × (2005-2010), and −6.43% year −1 in 2011-2018, suggesting rapid acceleration of glacier shrinkage even in present days.…”
Section: Cryospheric Water Under Future Climate Changementioning
confidence: 99%
“…Often, hydropower comes largely from cold water, originating from ice/snow melt in the mountain areas subject, to rapid cryosphere wasting due to global warming [7]. This could be a concern, especially for the Alps, with a large share of hydropower depending upon cryosphere water.…”
Section: Introductionmentioning
confidence: 99%
“…The trends observed in all the projections indicated significant changes to the current situation: the future melt-and rainfall-runoff will increase during spring but decline during summer [1]. Stucchi et al (2019) studied climate change impact on the Sabbione (Hosandorn) glacier, in the Piemonte region of Italy, and the homonymous reservoir, which collects water from ice melt, projecting forward hydrological cycle under properly downscaled climate change scenarios until 2100. They concluded that the decrease of cold water in this area, paradigmatic of the present state of hydropower in the Alps, and subsequent considerable hydropower losses under climate change, claims for adaptation measures [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation